1998
DOI: 10.1017/s000748530002589x
|View full text |Cite
|
Sign up to set email alerts
|

Does a repellent effect contribute to reduced levels of insect activity in dung from cattle treated with ivermectin?

Abstract: A two-year pitfall trapping study was performed to test the preference of coprophilous beetles (Hydrophilidae, Scarabaeidae, Staphylinidae) for dung from untreated cattle versus dung from cattle treated topically one or four weeks previously with a recommended dose of ivermectin in a pour-on formulation. In 1994, significantly more Aphodius fimetarius (Linnaeus) and A. distinctus (O.F. Miiller) at each of two sites were collected with dung from treated cattle. No differences were detected for other taxa. In 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 26 publications
1
36
0
3
Order By: Relevance
“…It has been reported that some dung-beetles were more attracted to dung from treated cattle than dung from control cattle (Wardhaugh and Mahon 1991, Holter et al 1993, Floate 1998b. Holter et al (1993) showed that Liatongus sp.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that some dung-beetles were more attracted to dung from treated cattle than dung from control cattle (Wardhaugh and Mahon 1991, Holter et al 1993, Floate 1998b. Holter et al (1993) showed that Liatongus sp.…”
Section: Discussionmentioning
confidence: 97%
“…The effects of fecal residues of antiparasitic drugs on the process of colonization by dungfeeding insects remain unclear (Floate et al 2005). Cattle dung from treated animals has been shown to be either more attractive (Wardhaugh & Mahon, 1991;Holter et al 1993;Lumaret et al 1994) or much less attractive than those from untreated animals (Floate 1998) to dung beetles in the field. A comparison of the chemical composition of dung odours revealed notable differences between the content of volatile compounds in dung of sheep, cattle, horse and deer (Dormont, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Dung was taken from untreated animals because antiparasitic drugs administered to herbivorous mammals possibly influence the attractiveness of their dung to insects (Wardhaugh & Mahon 1991;Floate 1998). The dung was collected fresh from several pats (immediately after defecation, before arrival of any coprophagous animals) and was thoroughly mixed together to homogenise it and to avoid possible differences in physical and chemical composition among individual pats.…”
Section: Field Tests Of Feeding Preferencementioning
confidence: 99%
“…Use of VMPs can affect colonization such that more or fewer insects may lay eggs in dung of treated livestock (Floate 1998a(Floate , 2007Holter et al 1993;Wardhaugh and Mahon 1991). The insecticidal activity of residues in such dung may be somewhat underestimated if it initially contains a larger starting population of insects relative to control dung and vice versa.…”
Section: Lethal Effectsmentioning
confidence: 99%